Designing Primers with a Plant Signal Peptide to Enhance the Expression of GBA1 in Transgenic Soybean Plants - Zainab Tuama Aldahlee (مجلة بغداد للعلوم, 2021)
Transgenic plants offer advantages for the manufacture of recombinant proteins with terminal mannose residues on their glycan chains. So plants are chosen as source of pharmaceutical products and for the development of alternative expression systems to produce recombinant lysosomal enzymes. In the present study the sequence of the natural cDNA encoding for the human lysosomal enzyme glucocerebrosidase (GCD) was modified to enhance its expression in soybean plants. The glucocerebrosidase gene signal peptide was substituted with that signal peptide for the Arabidopsis thaliana basic endochitinase gene to support the co-translational translocation into the endoplasmic reticulum (ER), and the storage vacuole. So, targeting signal from tobacco chitinase A, to facilitate GCD trafficking from the ER to the storage vacuole, appropriate primers were designed containing both an ER and vacuolar targeting signals, (VTS). Those primers were used for PCR amplification of the human GBA gene (Hu-GBA) gene from constructed PGEM-GBA plasmid which was cloned in the plant expression vector pCAMBIA1304. The resulted construct was transported in Agrobacterium tumefaciens strain LBA4404 and was used for transformation of cotyledon explants. After 5-day of seedling, cotyledons were cut and used as explants. After infection and co-cultivation, hygromycin B was added in selection media as a selective agent for the transformants cotyledons. The presence of the Hu-GBA transgene in the genomes of transgenic plants was determined by polymerase chain reaction PCR as a band of size1587 bp. The GBA mRNA expression in modified soybean was detected by qRT-PCR compared with control GBA mRNA.